If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3)(x + 1) + -1(x + 1)(4x + 2) = 0 Reorder the terms: (-3 + 2x)(x + 1) + -1(x + 1)(4x + 2) = 0 Reorder the terms: (-3 + 2x)(1 + x) + -1(x + 1)(4x + 2) = 0 Multiply (-3 + 2x) * (1 + x) (-3(1 + x) + 2x * (1 + x)) + -1(x + 1)(4x + 2) = 0 ((1 * -3 + x * -3) + 2x * (1 + x)) + -1(x + 1)(4x + 2) = 0 ((-3 + -3x) + 2x * (1 + x)) + -1(x + 1)(4x + 2) = 0 (-3 + -3x + (1 * 2x + x * 2x)) + -1(x + 1)(4x + 2) = 0 (-3 + -3x + (2x + 2x2)) + -1(x + 1)(4x + 2) = 0 Combine like terms: -3x + 2x = -1x (-3 + -1x + 2x2) + -1(x + 1)(4x + 2) = 0 Reorder the terms: -3 + -1x + 2x2 + -1(1 + x)(4x + 2) = 0 Reorder the terms: -3 + -1x + 2x2 + -1(1 + x)(2 + 4x) = 0 Multiply (1 + x) * (2 + 4x) -3 + -1x + 2x2 + -1(1(2 + 4x) + x(2 + 4x)) = 0 -3 + -1x + 2x2 + -1((2 * 1 + 4x * 1) + x(2 + 4x)) = 0 -3 + -1x + 2x2 + -1((2 + 4x) + x(2 + 4x)) = 0 -3 + -1x + 2x2 + -1(2 + 4x + (2 * x + 4x * x)) = 0 -3 + -1x + 2x2 + -1(2 + 4x + (2x + 4x2)) = 0 Combine like terms: 4x + 2x = 6x -3 + -1x + 2x2 + -1(2 + 6x + 4x2) = 0 -3 + -1x + 2x2 + (2 * -1 + 6x * -1 + 4x2 * -1) = 0 -3 + -1x + 2x2 + (-2 + -6x + -4x2) = 0 Reorder the terms: -3 + -2 + -1x + -6x + 2x2 + -4x2 = 0 Combine like terms: -3 + -2 = -5 -5 + -1x + -6x + 2x2 + -4x2 = 0 Combine like terms: -1x + -6x = -7x -5 + -7x + 2x2 + -4x2 = 0 Combine like terms: 2x2 + -4x2 = -2x2 -5 + -7x + -2x2 = 0 Solving -5 + -7x + -2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '-1'. -1(5 + 7x + 2x2) = 0 Factor a trinomial. -1((5 + 2x)(1 + x)) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-2.5, -1}
| 3w+1=77 | | (2x+5)*7=4x+57 | | a=18x^2 | | 4x+5=-7x+8 | | 47x(103+19)= | | -1-3b=-10-6b | | 180-2x=4 | | X^2+49=1024 | | u+12=31 | | 2x+5*7=4x+57 | | 7+5x=-13 | | 4x-2x=180 | | 5x^2+12=5x | | 3(y+6)=13 | | 6+4x=-58 | | (a+b)+2a=180 | | 1+8+x=23 | | 8.3=4k-2.4 | | x^4-4x^3+4x^2-16x=0 | | Y=8x+4.9 | | -6(3x+8)=-18x-48 | | x^4-4x^3+4x^2=16x | | 4(-2x+5)= | | 175-4p=375 | | 0=w^2-3w-1890 | | Y=10sin | | 4x+6=2x-30 | | 4k+2(5k-6)=-3-39 | | 6x-54=-24x | | 3(x-2)=5(x+8) | | 24-3k=-2k | | 6-6=8x+4x |